Kitchen garden: Perceived role and utilization among rural households in Mandya, Southern Karnataka - Sheethal MP; Shashikantha SK; Neeta PN; Shwetha Hariba (Asian Journal of Medical Sciences, 2023)
Background: Diversified diet is the key to combat micronutrient deficiency in India. Kitchen garden is a sustainable approach to provide diversified diet in rural area. Aims and Objectives: The objectives of this study were to assess the utilization and perception of kitchen garden use among the households in rural area. Materials and Methods: A community-based cross-sectional study carried out among women in the age group 18–65 years in Nagamangala was asked about the details on awareness and utilization of kitchen garden. Results: One-third of the study subjects were in the age group 30–40 years. About 18.2% of them were involved in some form of agriculture related work. Around 64% of the households had space available for kitchen garden. About 54% households had kitchen garden and 95% of the subjects used their kitchen garden products for self-use. Conclusion: Having kitchen garden contributes to household food security by providing direct access to food that can be easily harvested, prepared, and consumed.